Fencing the bear? Explaining US foreign policy towards Russian interventions. Issue 3 (1st September 2016) - Böller, Florian; Werle, Sebastian
ABSTRACT: Despite the burgeoning literature on Russia's renewed power politics, little attention has been paid to the fact that US reactions towards Russia's military interventions were all but coherent. The USA has chosen weak measures in Georgia in 2008 (shaming) compared to its assertive response in Ukraine in 2014 (sanctions, hard deterrence). This article assesses the explanatory power of neorealist, liberal and constructivist theories for the variation in US reactions towards Russian interventions in Georgia and Ukraine. Our argument is that the constructivist perspective explains the cases best as it highlights the power and communality of normative assessments. The Ukraine crisis was perceived by the USA as a violation of core international norms, especially the non-use of force and the principle of territorial integrity. Relevant international norm carriers shared this assessment of the conflict. In contrast, the perception of the Georgian war centred on the issue of democracy promotion. While democracy is an important aim of US foreign policy, it does not summon the same normative importance as general principles of international law. Furthermore, the perception of the Georgian war remained contested among Western allies, which decreased the communality of the normative assessment.